Effects of Five-Week Resistance Training in Hypoxia on Hormones and Muscle Strength. (January 2016) - Yan, Bing; Lai, Xiangxun; Yi, Longyan; Wang, Yang; Hu, Yang
Abstract : Abstract: Yan, B, Lai, X, Yi, L, Wang, Y, and Hu, Y. Effects of five-week resistance training in hypoxia on hormones and muscle strength. J Strength Cond Res 30(1): 184–193, 2016—The effects of different levels of systemic hypoxia on hormonal responses, strength, and body composition to 5-week resistance training were investigated. Twenty-five male subjects were randomly assigned into 3 experimental groups that performed 10 sessions (2 sessions per week) of barbell back squat (10 repetitions, 5 sets, 70% 1 repetition maximum [RM]) under normoxia (NR, Fi O2 = 21%) and hypoxia (HL, Fi O2 = 16%; HH, Fi O2 = 12.6%). Serum growth hormone (GH), testosterone (T), and cortisol (C) concentrations were measured before (Pre) and at 0 (T-0), 15 (T-15), 30 (T-30) minutes after exercise in the first and last training sessions. One repetition maximum, isometric knee extension, isometric leg press (LP), and body composition were evaluated before and after the protocol. In the first session, GH of HH ( p < 0.01) and HL ( p < 0.01) was higher than NR at T-0. In the last session, only GH of HH was higher than NR at T-0 ( p ⩽ 0.05); meanwhile, T/C ratio of HH was higher than NR at Pre ( p < 0.01), T-0 ( p < 0.01), and T-15 ( p ⩽ 0.05). Following the training protocol, HH showed greater ( p ⩽ 0.05) improvement of isometric LP strength compared with NR; lean body mass was increased in the hypoxia groups only. Moderate-intensity resistance training performed in severe hypoxia (Fi O2 = 12.6%) induced greater GH responses and isometric strength gains in LP than that in NR. Fi O2 of 12.6% was recommended when performing the moderate-intensity resistance training under systemic hypoxia.